2010
DOI: 10.1177/0146167210378852
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and the Need to Belong

Abstract: People who experience a strong need to belong might be particularly inclined to forgive wrongdoings to preserve social bonds. Three studies that utilized different methods and measures of forgiveness consistently demonstrated this is not the case. The authors found that individuals high in the need to belong report practicing forgiveness with less frequency and value it no more than those low in the need to belong (Study 1). In Study 2, they found that satisfying the need to belong led participants to express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In the interest of triangulation (e.g., Campbell & Fiske, 1959; Sackett & Larson, 1990), we used different measures of need to belong in the two studies. In Study 1, we used a scale of need to belong (Leary et al, 2013), which measures both the desire for belongingness and worry about experiences that connote a lack of acceptance (Barnes, Carvallo, Brown, & Osterman, 2010). In Study 2, we used a scale of fear of isolation that measures emotional responses associated with real or potential rejection (Hayes et al, 2013).…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…In the interest of triangulation (e.g., Campbell & Fiske, 1959; Sackett & Larson, 1990), we used different measures of need to belong in the two studies. In Study 1, we used a scale of need to belong (Leary et al, 2013), which measures both the desire for belongingness and worry about experiences that connote a lack of acceptance (Barnes, Carvallo, Brown, & Osterman, 2010). In Study 2, we used a scale of fear of isolation that measures emotional responses associated with real or potential rejection (Hayes et al, 2013).…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…This study connects to that line of work, but extends it in three important ways. First, we focused on belongingness needs, thought to be fundamental to human beings, and whose impact has been documented across a range of contexts (Barnes, Carvallo, Brown, & Osterman, 2010;Bastian & Haslam, 2010;Gardner et al, 2000). Second, we pinpointed the mechanism that drives the effects of belongingness on negotiators' economic outcomes.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Carvallo and Gabriel (10) in their study revealed that those with dismissive bonding style felt the need for acceptance by others and belonging. Additionally, individuals with high need to belong may have an anxious bonding style [12]. The need to belong was also found to be related to perfectionism expected of themselves and others, shyness [11], reputation [13], self-talk, loneliness [14], mental health [15], social inhibition, internalizing problems [16], tendency to forgive, self-esteem [12], life satisfaction [14], narcissism [17] and well-being [18].…”
Section: Introductionmentioning
confidence: 99%